Suppressor of IKKɛ is an essential negative regulator of pathological cardiac hypertrophy - Ke-Qiong Deng (Nature Portfolio, 2016)
Identifying pathways that cause pathological cardiac hypertrophy holds great therapeutic potential. Here the authors discover one such pathway and show that SIKE, an inhibitor of interferon signalling, prevents pathological but not physiological cardiac hypertrophy by interacting with TBK1 and modulating the TBK1/AKT signalling in rodents and monkeys.